Classes of Sexual Identity, Homophobia, and Sexual Risk among Black Sexual Minorities in HPTN 061. Issue 5 (13th June 2021) - Turpin, Rodman; Dyer, Typhanye; Watson, Lakeshia; Mayer, Kenneth
ABSTRACT: Homophobia is associated with sexual risk among sexual minorities, including Black sexual minority men, though experienced homophobia may differ across sexual identities. We conducted latent class analysis of sexual identities and experienced homophobia associated with sexual risk, and tested mediators of this association. We used longitudinal data from the HIV Prevention Trials Network Study 061 (n = 1, 553). We generated rate ratios between baseline latent classes of experienced homophobia and sexual identity and 12-month outcomes: Condomless receptive anal intercourse (CRAI), number of partners, and transactional sex. Mediators included 6-month internalized homophobia, depression, social support, and substance use. We selected the following 7-class model: "Bisexual, rare homophobia" (reference), "Mixed identities, mixed homophobia", "Bisexual, frequent homophobia", "Heterosexual/Same-gender loving, frequent homophobia", "Gay, frequent homophobia", " Gay/Same-gender loving, frequent homophobia, " and "Gay, rare homophobia." All other classes had greater CRAI than the reference. For bisexual/mixed/heterosexual classes, approximately 20% of this association was positively mediated through our mediators ( p < .05). The Heterosexual/Same-gender loving class had the largest proportion mediated through internalized homophobia. For gay-identifying classes, mediation was marginally significant (.05 <  p < .10). Classes of sexual identity and experienced homophobia were associated with CRAI among Black sexual minority men, partially mediated through internalized homophobia, depression, social support, and substance use.